Compendium of social statistics and indicators international migration statistics in the ESCWA region - United Nations. Economic and Social Commission for Western Asia. (New York United Nations, 2009)
"The ninth issue of the Compendium brings together information on international migration statistics in fourteen ESCWA member countries ... Divided into three chapters, the publication presents a set of reviewed statistics and indicators. Chapter I provides background information on international migration, while chapter II sets out migration international data, presented in tables and graphs for ease of reference, and offers both comparative and country-specific analysis. Chapter III sets out concluding commentary on the issue of migration status and indicators in the region. In addition, the Compendium includes three annexes: the first is a glossary; the second is a compilation of tables, primarily on stocks and flows; and the third is a listing of the United Nations recommended core tabulations on international migration that originally appeared in the 1998 United Nations Recommendations on Statistics of International Migration, Revision 1."--Preface.
"E/ESCWA/SD/2009/12."
"Sales No. E.10.II.L.1"--P. [4] of cover.
Full text also available online
Keywords: Middle East -- Emigration and immigration -- Statistics